Scope of electricity efficiency improvement in Switzerland until 2035 - Boris Krey (University of Zurich, Socioeconomic Institute, 2008)
This study uses Markowitz mean-variance portfolio theory with forecasted data for the years 2005 to 2035 to determine efficient electricity generating technology mixes for Switzerland. The SURE procedure has been applied to filter out the systematic components of the covariance matrix. Results indicate that risk-averse electricity users in 2035 gain in terms of higher expected return, less risk, more security of supply and a higher return-to-risk ratio compared to 2000 by adopting a feasible minimum variance (MV) technology mix containing 28 percent Gas, 20 percent Run of river, 13 percent Storage hydro, 9 percent Nuclear, and 5 percent each of Solar, Smallhydro, Wind, Biomass, Incineration, and Biogas respectively. However, this mix comes at the cost of higher CO2 emissions.
Keywords: C32; G11; Q49; C23; 330; Efficiency Frontier; Herfindahl-Hirschman Index (HH); Power Generation; Mean-Variance Portfolio Theory; Seemingly Unrelated Regression Estimations (SURE); Shannon-Wiener Index (SW); Energieversorgung; Technische Effizienz; Konzentrationsindex; Portfolio-Management; Schweiz